Effect of Organics and Nanoparticles on CO2-Wettability of Reservoir Rock; Implications for CO2 Geo-Storage - Ali, Muhammad (Curtin University, 2021)
In this study, we have investigated the effect of various organic acids (hexanoic, lauric, stearic, and lignoceric acid) and nanoparticles (silica and alumina) on various geo-storage formations (sandstone, carbonate, and cap-rock) by conducting contact angle measurements at various physio-thermal conditions. The result showed that geo-storage minerals became super-hydrophobic in the presence of organic acids, thus, less CO2 trapping capacity and nano-fluids have significantly turned organic-aged geo-storage minerals to intermediate-wet, thus, increased CO2 trapping capacity.